HEMODYNAMIC AND STRUCTURAL PECULIARITIES OF THE PROSTATE GLAND IN MEN AGED BETWEEN 22 AND 35 - Геращенко, С.Б.; Грицуляк, Б.В.; Грицуляк, В.Б.; Поливкан, М.І.; Халло, О.Є. (World of Medicine and Biology, 2015)
Using the methods of ultrasonic diagnostics and histology, we have researched the hemodynamic and structural peculiarities of the prostate in 19 men aged between 22 and 35. We have found out that in the given age the volume of the said organ is – (21.1±2.0) cm³, the weight – (21.9±1.8) g, the width - (37.4±2.0) mm, the thickness – (24.5±1.8) mm and the length - (22.8±2.1) mm. The peak systolic blood flow velocity is (18.85±3.0) cm/sec and the diastolic one – (5.76±0.03) cm/sec, the resistance index is (0.71±0.02) conv. units and the volumetric flow rate – (0.060±0.012) l/min. Histologically, the prostate of men of a mature age is well developed and has an apparent lobulate structure. The secretory segments of the prostate lobules are alveolar-tubular, the epithelium of the terminal parts of glands is prismatic, with the ratio of glandular parenchyma to elastic muscular stroma between 69.9 % and 30.1 %. By means of Doppler color flow imaging, we have obtained a clear image of prostatic blood vessels in normal condition. The capsular blood vessels in the transverse section are represented by separate dotted color signals with a diameter of (3.0±0.2) mm. The urethral arteries and periurethral veins have a straight direction and are symmetrically located in the periurethral area. Next to the prostate gland along the anterior and the lateral border, one can observe tubular vascular structures of venous plexuses. The vein diameter usually does not exceed (4.0±0.1) mm.